2009
DOI: 10.1016/j.patrec.2008.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative fusion of normalised scores in multimodal biometrics

Abstract: A new approach to enhancing the accuracy of multimodal biometrics is investigated. The proposed approach, which involves combining score normalisation and qualitative-based fusion, is shown to considerably improve the accuracy of multimodal biometrics under different data conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…On the contrary, in the right panel of Figure 10 , since the distance values are normalized, it allows us to use a single threshold value for all modalities so that parameter tuning procedure can be simplified. This normalization procedure is similar to score normalization [ 51 , 52 ]. Algorithm 1 Majority Voting Based Decision Level Fusion For the given threshold , the number of classifier and the feature vector , the decision level majority voting accepts if where outputs the greatest integer that is less than or equal to and is an individual classifier such that
…”
Section: Methodsmentioning
confidence: 99%
“…On the contrary, in the right panel of Figure 10 , since the distance values are normalized, it allows us to use a single threshold value for all modalities so that parameter tuning procedure can be simplified. This normalization procedure is similar to score normalization [ 51 , 52 ]. Algorithm 1 Majority Voting Based Decision Level Fusion For the given threshold , the number of classifier and the feature vector , the decision level majority voting accepts if where outputs the greatest integer that is less than or equal to and is an individual classifier such that
…”
Section: Methodsmentioning
confidence: 99%
“…Bendris et al introduced quality measures in audio-visual identity verification [18]. Alsaade et al showed that score normalization and quality-based fusion improve the accuracy of multimodal biometrics [2]. Optimal integration weight estimation using least squares technique was reported in [19].…”
Section: Previous Workmentioning
confidence: 99%
“…This average distance is not an adequate performance measure since a large value ofρ 2 does not imply that the classes are well separated. The performance measure well suited to express the separability of classes is the ratio between inter-class and intra-class distance [29].…”
Section: Estimation Of Inter-/intra-class Distancementioning
confidence: 99%
See 1 more Smart Citation
“…[5]. Alsaade et al in 2009 showed that score normalization and quality-based fusion improves the accuracy of multimodal biometrics [3]. Optimal integration weight estimation using least squares technique was reported in [23].…”
Section: Introductionmentioning
confidence: 99%